Family History in Young Patients With Stroke. Issue 7 (July 2015) - Thijs, Vincent; Grittner, Ulrike; Dichgans, Martin; Enzinger, Christian; Fazekas, Franz; Giese, Anne-Katrin; Kessler, Christof; Kolodny, Edwin; Kropp, Peter; Martus, Peter; Norrving, Bo; Ringelstein, Erich Bernd; et al.
Abstract : Background and Purpose—: Family history of stroke is an established risk factor for stroke. We evaluated whether family history of stroke predisposed to certain stroke subtypes and whether it differed by sex in young patients with stroke. Methods—: We used data from the Stroke in Fabry Patients study, a large prospective, hospital-based, screening study for Fabry disease in young patients (aged <55 years) with stroke in whom cardiovascular risk factors and family history of stroke were obtained and detailed stroke subtyping was performed. Results—: A family history of stroke was present in 1578 of 4232 transient ischemic attack and ischemic stroke patients (37.3%). Female patients more often had a history of stroke in the maternal lineage ( P =0.027) than in the paternal lineage. There was no association with stroke subtype according to Trial of Org 10172 in Acute Stroke Treatment nor with the presence of white matter disease on brain imaging. Patients with dissection less frequently reported a family history of stroke (30.4% versus 36.3%; P =0.018). Patients with a parental history of stroke more commonly had siblings with stroke (3.6% versus 2.6%; P =0.047). Conclusions—: Although present in about a third of patients, a family history of stroke is not specifically related to stroke pathogenic subtypes in patients with young stroke. Young women with stroke more often report stroke in the maternal lineage. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00414583. Abstract : Supplemental Digital Content is available in the text.